n Kollokasie-metode vir die numeriese oplossing van integraalvergelykings - Loots, M. J. P.(Marthinus Johannes Petrus) (Stellenbosch : Stellenbosch University, 2012)
Proefskrif (M. Sc.) -- Universiteit van Stellenbosch, 1975.